School adolescents and the health in school program: An integrative review (Research, Society and Development, 2022)
This research focused on knowing the importance of the actions promoted by the (School Health Program) PSE from the perspective of adolescents, in the light of the literature. Therefore, the research is characterized by an integrative literature review with a qualitative approach. The results showed that topics such as sexuality, anthropometric assessment and the participation of nurses were positive findings according to the adolescents, while the other topics proposed in the PSE guidelines were not evident as health policies related to the environment and combating violence . It is concluded that the school is a place conducive to access for adolescents. Actions aimed at health promotion and disease prevention could become even more joint and continuous through the partnership between health professionals, teachers and the family in order to contribute to the change of behavior among adolescents, thus collaborating for the your health and quality of life. It is expected that the theme presented will provide questions for future research that will contribute to the health of adolescents in the school environment.